Rozwiązane

13/86
A) (-2+9)•(-3)=
B) (-4-8)•(7-11)=
C) -4•5-7•(-2)=
D) 3-(-5)
____. =
-4
E) (-16-8):(-4+10)=
F) (-2)•(5-9)-(-7+3)=
G) -7+8:(-2)-3•(-5)=
H) (14-19)-(27-(-3)
__________. =
20-25



Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

(-2+9)•(-3)= 7*(-3)=-21

(-4-8)•(7-11)= - 12*4=-48

-4•5-7•(-2)=-20-(-14)=-20+14=6

3-(-5)

____. =8/-4=-2

-4

(-16-8):(-4+10)= - 24:6=-4

(-2)•(5-9)-(-7+3)= - 2*(-4)-(-4)=8+4=12

-7+8:(-2)-3•(-5)=-7+(-4)-(-15)=-11+15=4

(14-19)-(27-(-3)

__________. =-5-30/-5=-35/-5=7

20-25

Twoja odpowiedź